Efforts to Grow Students' Social Awareness through Mutual Cooperation as an Implementation of Bhinneka Tunggal Ika at MI Mambaul Ulum Al-Murtadlo - Hasanah, Uswatun; Fitrianingsih, Uun; Rahmawati, Wahidah; Rosyida, Vina Nur; Khasanah, Uswatun (MANDAILING GLOBAL EDUKASIA, 2025)
Mutual cooperation is one of the social values ​​that characterizes the Indonesian nation in strengthening unity and oneness in various kinds of diversity, namely the diversity of religion, ethnicity and culture. This value is in line with the motto Bhinneka Tunggal Ika which emphasizes the importance of unity in various diversities. This article was created with the aim of analyzing how mutual cooperation activities can foster students' social awareness and strengthen their understanding of the meaning of Bhinneka Tunggal Ika. This article was created using a qualitative descriptive method with data collection techniques in the form of observations conducted on students of Madrasah Ibtidaiyah Mambaul Ulum Al-Murtadlo. The results of this article show that student involvement in mutual cooperation activities such as cleaning the school environment, helping friends in need and community service in the school environment and the community. This mutual cooperation is also able to increase a sense of caring, cooperation and social responsibility. In addition, students better understand the importance of respecting differences in religious culture and social background. The implementation of mutual cooperation not only forms positive character in students but is also an effective means of instilling the values ​​of tolerance, togetherness and unity in accordance with the meaning of Bhinneka Tunggal Ika.